Viable Sweetpotato Technologies for Africa (VISTA) Tanzania Project - International Potato Center (2017)
During the past year, VISTA Tanzania completed and disseminated its formative gender evaluation study. The project provided 14,835 households with clean planting material and nutrition education counselling. A total of 146 community health workers received refresher training on nutrition education and orange-fl eshed sweetpotato (OFSP) recipe preparation, while 30 seed and root entrepreneurs received refresher training on agribusiness development.